Analisis Strategi Pembelajaran Project Based Learning Dalam Meningkatkan Kreativitas Mahasiswa Jurusan KPI Semester 6 - Juni Hidayati Batubara; Izzatul Muthmainnah; Alya Hamzah Panggabean; Natasya Natasya; Masnawari Harahap (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Project Based Learning is a learning model that makes students the subject or center of learning, emphasizing the learning process which has a final result in the form of a product/project. This research aims to describe the use of project-based learning methods in terms of increasing student creativity. The approach used is a qualitative method, namely interviews conducted with sources from students, library research is carried out by studying book references, articles and browsing the internet. Data collection by utilizing this bibliography is in order to better support the research object.